Corticotropin releasing factor up‐regulates the expression and function of norepinephrine transporter in SK‐N‐BE (2) M17 cells. (18th August 2015) - Huang, Jingjing; Tufan, Turan; Deng, Maoxian; Wright, Gary; Zhu, Meng‐Yang
Abstract: Corticotropin releasing factor (CRF) has been implicated to act as a neurotransmitter or modulator in central nervous activation during stress. In this study, we examined the regulatory effect of CRF on the expression and function of the norepinephrine transporter (NET) in vitro . SK‐N‐BE (2) M17 cells were exposed to different concentrations of CRF for different periods. Results showed that exposure of cells to CRF significantly increased mRNA and protein levels of NET in a concentration‐ and time‐dependent manner. The CRF‐induced increase in NET expression was mimicked by agonists of either CRF receptor 1 or 2. Furthermore, similar CRF treatments induced a parallel increase in the uptake of [ 3 H] norepinephrine. Both increased expression and function of NET caused by CRF were abolished by simultaneous administration of CRF receptor antagonists, indicating a mediation by CRF receptors. However, there was no additive effect for the combination of both receptor antagonists. Chromatin immunoprecipitation assays confirm an increased acetylation of histone H3 on the NET promoter following treatment with CRF. Taken together, this study demonstrates that CRF up‐regulates the expression and function of NET in vitro . This regulation is mediated through CRF receptors and an epigenetic mechanism related to histone acetylation may be involved. This CRF‐induced regulation on NET expression and function may play a role in development of stress‐related depression and anxiety. This study demonstrated that corticotropin release factor (CRF) up‐regulated the expression and function of norepinephrine transporter (NET) in a concentration‐ and time‐dependent manner, through activation of CRF receptors and possible histone acetylation in NET promoter. The results indicate that their interaction may play an important role in stress‐related physiological and pathological status. Abstract : This study demonstrated that corticotropin release factor (CRF) up‐regulated the expression and function of norepinephrine transporter (NET) in a concentration‐ and time‐dependent manner, through activation of CRF receptors and possible histone acetylation in NET promoter. The results indicate that their interaction may play an important role in stress‐related physiological and pathological status.